Neoadjuvant therapy with cadonilimab in a patient with MSI-H/dMMR colorectal cancer: a case report - Zhou, Jingrui; Chen, Weimin; Wang, Jue; Chen, Ziwei; Guo, Guanghui; Yang, Tao; Shen, Tao (Frontiers in Oncology, 2026)
Neoadjuvant immunotherapy for mismatch repair-deficient/microsatellite instability-high (dMMR/MSI-H) colorectal cancer continues to accumulate compelling clinical evidence. This report presents the case of a 37-year-old female who presented with moderate anemia (hemoglobin: 69 g/L) and was subsequently diagnosed with dMMR/MSI-H descending colon cancer. Following nine cycles of cadonilimab, a novel PD-1/CTLA-4 bispecific antibody, the patient achieved significant tumor regression and subsequent pathological complete response (pCR) after surgery, with a favorable safety profile observed throughout the treatment course. This case provides valuable clinical evidence supporting the efficacy and safety of cadonilimab in the neoadjuvant setting for dMMR/MSI-H colorectal cancer.